IMF Survey, Volume 32, Issue 18. (IMF Survey; IMF Survey, 2003)
The IMF announced October 10 that its Executive Board had agreed on measures to enhance further the transparency of the institution, in particular by promoting the publication of more country documents. The agreement will be implemented following the Board's adoption, in the coming weeks, of specific amendments to its previous decision on transparency.